Solvent-induced two Dy2 compounds with different structures showing distinct slow magnetization relaxation behaviors. (1st March 2019) - Xue, Yun-Shan; Yang, Jia-Xing; Han, Ju-Qing; Liu, Su-Su; Cui, Ying-Ying; Tan, Yu; Hua, Yu-Peng; Wang, Wen-Min
Graphical abstract: Two new Dy2 compounds based a polydentate Schiff base ligand have been synthesized by using two different solvent systems. Magnetic property measurements indicate that they exhibit distinct slow magnetic relaxation behaviors (Δ E /kB  = 0.87 K for1 and Δ E /kB  = 18.68 K for2 ). This work revealed that the different solvent induced slight disparate structural and magnetic behaviors of two Dy2 compounds, which may provide an effective approach for tuning slow magnetization relaxation behaviors in polynuclear Ln-clusters. Abstract: Two new Dy2 compounds, namely, [Dy2 (dbm)4 (H2 L)(CH3 O)(CH3 OH)] (1 ) and [Dy2 (dbm)5 (H2 L)] (2 ) (dbm = dibenzoylmethane, H3 L = (2E, N′E)-2-(hydroxyimino)-N′-(pyridin-2-ylmethylene)propanehydrazide, based a polydentate Schiff base ligand have been synthesized, structurally and magnetically characterized. The single-crystal X-ray diffraction research show that both compounds1 and2 are binuclear structures. The only difference is that two methanol molecules coordinated to Dy(III) ion in1 instead of a dbm − coordinated to Dy(III) ion in2 . Magnetic property measurements indicate that they exhibit distinct slow magnetic relaxation behaviors (Δ E /kB  = 0.87 K for1 and Δ E /kB  = 18.68 K for2 ). This work revealed that the different solvent induced slight disparate structural and magnetic behaviors of two Dy2 compounds, which may provide an effective approach for tuning slow magnetization relaxation behaviors in polynuclear Ln-clusters.